Mô hình cơ sở dữ liệu dạng khối - Huy, Nguyễn Xuân; Thắng, Trịnh Đình (Journal of Computer Science and Cybernetics, 2016)
At the present time, some types of database models are considered, in which three types of database models are objects of interest: Hierachiral model, Network model and Relational model. This paper introduces a new model for databases, which called a database model of block form. Some basis concepts and block form - relational algebra are introduced for this model. Some of properties related to keys of block schema and block form - relational algebra are claimed and proved. It is shown that the relational database model is special case of the database model of block form in which each relation is a block with the index set, containing only one element.